Manipulation of the kinematic chaln using visual biofeedback - Mulloy, F.; Mullineaux, D. R.; Irwin, G. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
Feedback has been shown to be an influential component in skill development, yet this has not been assessed in movements involving an explosive proximal to distal sequencing pattern. Novices (n=14) were introduced to a lunge touch task. Visual biofeedback were given on the timing and magnitude of rear leg kinematics. Results showed that those who received feedback adapted their movement patterns by developing extension velocity magnitudes in a summative pattern (pre v post, mean f SD peak ankle angular velocity: biofeedback; 479 ± 181 v 689 ± 11 7, control; 468 ± 106 v 477 ± 84 deg/s), resulting in greater horizontal impulse (mean ± SD: biofeedback; 1.17 ± 0.60 v 1.7 ± 0.89, control; 1.33 ± 0.33 v 1-49 ± 0.33 N*s/kg). The changes were retained after six weeks. These results demonstrate that knowledge of performance based biofeedback interventions alone are effective in developing whole limb contributions in an explosive task.